Wide-Range Tunable Narrow Band-Stop Filter Based on Bilayer Graphene in the Mid-Infrared Region - Yindi Wang; Hongxia Liu; Shulong Wang; Ming Cai (IEEE Photonics Journal)
In this paper, a tunable graphene-based band-stop filter in the mid-infrared region was demonstrated, which consists of periodic structure based on bilayer graphene nanoribbons. Due to the unique tunable Fermi level of graphene, the resonance wavelength of the filter can be tuned over a wide range (10020 nm–15100 nm) with the applied voltage varying from 1 V to 5 V, realizing selectivity and tunability. The results also confirm that the presented structure can realize a narrow-band selective filter with a 3 dB bandwidth of 40 nm. Furthermore, the trough transmittance of stopband is close to zero and the transmittance of passband remains above 96.7%. Moreover, this filter is quite robust to the incident angles. The stopband is still extremely narrow as the incident angle varies from 0° to 60°, realizing wide-angle filtering. In addition, the fabrication processing and fabrication error tolerance are investigated, and it has proved that the filter is quite tolerant to fabrication deviations. Hence, the work has potential applications in narrowband filters, active plasmonic switches, and sensors in the mid-infrared region.